Perancangan User Experience Aplikasi Pembuatan Konten Tiktok untuk Marketing Produk UMKM menggunakan Metode Human-Centered Design - Nisrina Dhia Ufaira; Ratih Kartika Dewi; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Pandemics in the era of globalization require MSMEs to be able to maintain their existence amid the onslaught of the global economy, so they must have a good marketing strategy. Based on data quoted from Kompas news media, every month Tiktok managed to have 14.3 million new active users so it is predicted to have more than one billion monthly active users in May 2022. TikTok's growth will gradually move into commercialized social media and allow its users to earn revenue from in-app purchases, so TikTok can be considered a fairly ideal platform for marketing products. Unfortunately, not many MSMEs are familiar with product marketing through TikTok due to lack of information, there are still few courses that discuss Tiktok marketing, especially in Indonesian and there are still few tools that can help MSMEs in creating content marketing. The method used in this study is human-centered design because this research has a focus on solving problems about lack of knowledge, lack of learning facilities for MSMEs about Tiktok marketing, and lack of tools that can help MSMEs. This method is considered suitable because it is successfully applied to previous studies with good evaluation results. The final result of this study is a high-fidelity prototype that will be used to conduct usability testing. From the test obtained the results of the effectiveness aspect with completion rate metric 83.57%, overall relative efficiency aspect of 100% and time-based efficiency 0.135 goals/sec, and aspects of user satisfaction using the SUS questionnaire of 83.5.